Comissões parlamentares de inquérito e jurisdição constitucional: os usos políticos da mídia e a perda de legitimidade do estado - Braghirolli, Fernanda (Universidade do Vale do Rio do Sinos, 2009)
This research is a study of relations between the media and the judiciary. Here the goal, the use of Parliamentary Committees of Inquiry (CPIs) as an instrument of media policy, occurring thus the solapamento the legitimacy of the state arising from the struggle for hegemony in the political arena, especially in the field of action of the Constitutional Jurisdiction. Thus, the dynamics of political and media action is intended to produce an effect of destabilizing the institutions, the encroaching role of the judiciary to promote trials, without the protections and the instruments themselves of the judicial process, and to condemn in advance citizens called to testify in such commissions. There is the struggle of the media to legitimize itself as a political, not have, in fact, any interest in improving the institutions of the state, but in the dispute with the judiciary by the symbolic power of imposing the "truth" and the democratic exercise citizenship. To address the issue, the first chapter describes the
Keywords: comissões parlamentares de inquérito; legitimação do estado; mídia; jurisdição constitucional; legitimation of state; media; parliamentary committees of inquiry; jurisdiction constitutional; Ciências Sociais Aplicadas